Soil organic carbon and related properties under conservation agriculture and contrasting conventional fields in Northern Malawi - Manzeke-Kangara, Muneta G.; Ligowe, Ivy S.; Tibu, Austin; Gondwe, Timothy N.; Greathead, Henry M. R.; Galdos, Marcelo V. (Frontiers in Soil Science, 2025)
Conservation agriculture (CA) is widely promoted as an agroecology-based approach for soil conservation. Several studies have focused on effects of CA on crop yields and soil moisture dynamics in sub-Saharan Africa, with limited focus on effects of CA on soil organic carbon (SOC) and associated fractions. We collected representative soil samples from 30 paired farms under CA and conventional tillage in Mzimba district, north of Malawi to determine effects of tillage and soil depth on soil physico-chemical properties, total SOC, and organic carbon fractions. Undisturbed soil cores were collected for bulk density measurements. Different SOC pools were determined using the soil fractionation method, while soil physico-chemical analyses were conducted using standard laboratory methods on disturbed soil samples. Soil organic carbon content ranged from 0.4-1.8% in CA plots. This was significantly larger than SOC contents of 0.4-1.5% measured under conventional tilled plots. Tillage type and soil depth had significant interaction effects on SOC. For example, larger contents of SOC were measured at depths of 0-10 cm compared to 10-30 cm under CA plots. Soil depth had significant effects on most soil properties compared to tillage. Examples include Heavy Particulate Organic Matter-Carbon (POM-C) fraction, Mineral Associated Organic Matter-Carbon (MAOM-C), nitrogen in MAOM fraction and nitrogen in the Light POM fractions. These were larger in the 0-10 cm soil depth than in the 10-30 cm soil depth. In contrast, tillage type only had significant effects on the Heavy POM-C and MAOM-C fractions, which were larger under CA than conventional tilled plots. Conservation agriculture showed capacity to improve total SOC and its associated fractions, a finding relevant towards understanding effects of land management on carbon storage. However, challenges of competing residue use as feed, mulch, and fuel continue to impede mulching under CA systems. Longer term studies and use of alternative mulching options could be employed to recognise noticeable changes in other SOC beneficial pools in fields under CA.